Adherence to care transitions recommendations among high‐risk hospitalized older patients. Issue 6 (26th March 2021) - Reyes, Bernardo; Diaz, Sanya; Engstrom, Gabriella; Ouslander, Joseph
Abstract: Background/Objectives: Evidence on the effectiveness of inpatient hospital geriatric consultation is scant, and it is unknown whether adherence to specific recommendations will improve care and patient outcomes. This study was conducted to provide insights from a quality improvement project that may help guide further improvements in the effectiveness of these consultations made as a component of a care transitions program (CTP). Design: Secondary analysis of the implementation of a multicomponent CTP for high‐risk hospitalized patients aged 75 and older. Setting: A 400‐bed community teaching hospital. Participants: Two hundred and two patients admitted to non‐ICU beds who met high‐risk criteria. Intervention: Inpatient comprehensive geriatric consultation including care transition recommendations, telephone and in‐person follow‐up weekly for 4 weeks after discharge, and collaboration with post‐acute organizations and primary care and specialist physicians to implement recommendations. Measurements: Primary outcomes for this analysis was 30‐day hospital readmissions and adherence to transition of care recommendations. Results: The 142 patients with at least one post‐discharge visit received 936 care transition recommendations. Overall, 663 (71%) of the 936 care transition recommendations were adhered to (71%). The adherence rate was lower in the 22 patients who were readmitted to the hospital within 30 days (63%) compared to 72% adherence in the 120 patients who were not readmitted. This was not a statistically significant difference, and there were no significant differences in the number and percent adherence in any recommendation category between the two groups. Conclusion: We found adherence to just over two‐thirds of care transition recommendations, similar to a small number of other studies. We did not find a relationship between the number of recommendations and adherence to them with 30‐day readmissions to the hospital. Future studies of CTPs should consider several strategies may enhance geriatric consultation care transitions recommendations and adherence to them, and improve patient outcomes.